A review on ESG investing: Investors' expectations, beliefs and perceptions - Roman Kräussl; Tobi Oladiran; Denitsa Stefanova (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
This study examines the recent literature on the expectations, beliefs and perceptions of investors who incorporate Environmental, Social, Governance (ESG) considerations in investment decisions with the aim to generate superior performance and also make a societal impact. Through the lens of equilibrium models of agents with heterogeneous tastes for ESG investments, green assets are expected to generate lower returns in the long run than their non- ESG counterparts. However, at the short run, ESG investment can outperform non-ESG investment through various channels. Empirically, results of ESG outperformance are mixed. We find consensus in the literature that some investors have ESG preference and that their actions can generate positive social impact. The shift towards more sustainable policies in firms is motivated by the increased market values and the lower cost of capital of green firms driven by investors' choices.
urn:nbn:de:hebis:30:3-681504
Keywords: 330; Environmental; Social; Governance; ESG; Performance; Sustainability; Social Impact; Greenwashing